Theme-based Lesson Plan for the Volunteers of After-school Program in Rumah Belajar Kagem, Jogjakarta - Dewi Riyanti, E; Nur Annisaa, W; Rahmaniati, Z (KnE Social Sciences, 2019)
Learning may come in many different ways. In Indonesia, learning activities can be carried out in formal, informal, and also non-formal institutions. As mentioned in Section 5, verse 26, item 2 of UU SISDIKNAS (the National Education Law), non-formal education is functioned to improve students’ potential with the emphasis on knowledge and functional skills’ mastery added with attitude enhancement and professional entity. In this case, the aforementioned characteristic is reflected in the after-school program in Rumah Belajar KAGEM. KAGEM is a non-profit institution established in 2012 to help children in Ngaglik, Sleman to have after-school activities. One distinctive characteristic offered by KAGEM is free-of-charge classes taught by volunteers. KAGEM’s volunteers are mostly university students and work for free in this institution. The volunteers are working on various topics that enables them to interactively disseminate ideas with the children. Nevertheless, most of them find it challenging to make proper lesson plan that is based on daily basis events. Thematic activities are brought up to put learning in real setting. To respond the issue, the researchers conducted a training for the volunteers of KAGEM that incorporates day-to-day issues to the after-school program. Under the university’s community service program, the researchers conducted observations and followed by training on making theme-based lesson plan which aimed to meet the needs of this institution. From the result of reflection given after the training, KAGEM’s volunteers find the training helpful and insightful, since there is limited chance offered to them for upgrading their teaching skills. They also feel more motivated and challenged to work on the volunteering duty and ready to dig out new approaches that suit the learners in Rumah Belajar KAGEM. Keywords: Lesson plan, after-school program, training